Pengelolaan Aplikasi Layanan Administrasi pada Kelurahan Argasunya - Garsandi, Akmal Maulana; Mulyawan; Dana, Raditya Danar; Kaslani; Tohidi, Edi (MEANS (Media Informasi Analisa dan Sistem), 2022)
Argasunya Village is a combined area of several Rukun Warga (RW). Government at the village and sub-district levels is an element of government that is directly related to the community. Kelurahan is also an administrative division under the subdistrict. The village office has not used the system in making a Business Certificate. Therefore, the author tries to make a service application for making a business certificate based on a web application with the hope of simplifying the procedures for making a business certificate, the author uses data sources (Observation and Interviews). The programming language used is PHP language with MySql database. For system design, the author uses the Prototype method. From the results of the tests carried out, the system functionality can run well and the making of online and onsite business certificates is appropriate and can run well..